RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PELELANGAN IKAN PADA KUD MINAJAYA SENDANGBIRU KABUPATEN MALANG - Sholikin, Muhammad Anas; Dwanoko, Yoyok Seby; Agustina, Rini (Department of System Information, 2025)
The web-based fish auction management information systemwas designed to address various problems arising from manual transactionmanagement at the Fish Auction Place (TPI) of Sendangbiru Hamlet, MalangRegency. The continued reliance on manual processes leads to calculationerrors, loss or damage of documents, and is time-consuming in transaction management, particularly in the lengthy and error-prone process of note creation. Each transaction requires the manual creation of several types ofnotes, thereby increasing the possibility of human error and the accumulationof unpaid notes. In this research, a User-Centered Design (UCD) approachalso using tools like MySql as main database and CodeIgniter framework wasused to ensure that the developed system truly aligns with the needs of users,such as fishermen, traders (bakul), and TPI managers. Evaluation using UserAcceptance Test (UAT), UAT evaluation results showed that the designedsystem meets feasibility criteria with high percentages in the aspects ofusability (87.5%), portability (94.38%), reliability (97%), business processsuitability (83.75%), and performance (91.87%). System show that the fishauction transaction process becomes faster, more transparent, and accurate,and it reduces the risk of errors that occur in the manual system. This systemprovides easier access for fishermen and traders to monitor transactions,simplifies data and information management for TPI managers. Thus, theimplementation of this system is improving the quality of fish auctionmanagement at TPI Sendangbiru Hamlet.